Anti-Inflammatory Activity of Choisya ternata Kunth Essential Oil, Ternanthranin, and Its Two Synthetic Analogs (Methyl and Propyl N-Methylanthranilates) - Boylan, Fabio (Elsevier, 2015)
Choisya ternata Kunth (Rutaceae) is native to North America where it is popularly known as "Mexican orange". In this study, the anti-inflammatory effects of the essential oil (EO) obtained from the leaves of C. ternata , one of its minor components (ternanthranin - ISOAN) and its two synthetic analogues (methyl and propyl N-methylanthranilate - MAN and PAN) were evaluated. Mice pretreated with the EO (EO) obtained from C. ternata leaves (3-100 mg/kg, p.o.), ISOAN, MAN or PAN (1-30 mg/kg, p.o.) and the reference drugs, morphine (1 mg/kg, p.o.) and acetylsalicylic acid (ASA, 100 mg/kg, p.o.), were evaluated in inflammation models such as formalin and subcutaneous air pouch models, with measurement of cell migration, exudate volume, protein extravasation, nitric oxide and proinflammatory cytokines. The EO from C. ternata significantly inhibited the time that the animals spent licking the formalin-injected paw in the second phase of the model at their higher doses (30 and 100 mg/kg, respectively). An inhibition of the inflammatory reaction induced after subcutaneous carrageenan injection into air pouch was also observed. In this model, the EO significantly reduced cell migration, exudate volume, protein extravased, and the increase in levels of inflammatory mediators (nitric oxide, TNF-α and IL-1β). ISOAN, MAN and PAN behaved in the same fashion at much smaller doses. Also, these molecules were able to show significant effects in the reduction of paw edema (at all tested doses) when the phlogistic agent was carrageenan, bradykinin, 5-HT, PGE2, C48/80 or 12-O-tetradecanoyl-phorbol- acetate (TPA). None of the tested doses had any effect in reducing histamine-induced edema. Our results indicate that the EO from C. ternata and anthranilate derivatives demonstrates an anti-inflammatory effect.
PUBLISHED
Netherlands
Keywords: Choisya ternata Kunth; Choisya ternata Kunth